Elucidating transgender students' experiences of microaggressions in social work programs: next steps for creating inclusive educational contexts. Issue 7 (3rd October 2019) - Austin, Ashley; Craig, Shelley L.; Dentato, Michael P.; Roseman, Shirley; McInroy, Lauren
ABSTRACT: Social work education globally expresses an unwavering commitment to promoting social justice and the amelioration of oppression. Nevertheless, mounting research suggests that social work programs (SWPs) may inadvertently perpetuate microaggressions toward individuals who are transgender and gender non-conforming (TGNC). This qualitative study elucidates experiences of TGNC social work students in North America. Grounded theory analysis revealed six key themes related to students' experiences of microaggressions within their SWPs: (1) structural oppression, (2) cisgender bias, (3) faculty knowledge gaps, (4) visible discomfort, (5) pervasive nature of transphobia, and (6) social exclusion. Despite the existence of educational and professional policies aimed at fostering transgender inclusive social work education and practice, results from this study underscore the need to take a closer look at the ways in which knowledge gaps, implicit cisgender biases, and existing practices and policies within SWPs inadvertently privilege the experiences of cisgender students and marginalize TGNC students. Key findings from the current study can be used to inform the implementation of transgender affirmative changes, contributing to efforts to eradicate transphobic bias within SWPs.